Atak Belirtisi Olarak Mani Tablosuyla Başvuran Bir Multiple Skleroz Olgusu - Yoldaş, Tahir; Ulvi, Hızır; Atmaca, Murad; Yiğiter, Remzi; Polat, Nilgün; Müngen, Bülent (Fırat University, 2002)
Multiple Skleroz'lu (MS) hastalarda, hastalığın seyri esnasında sık olarak çeşitli psikiyatrik bozukluklara rastlanılmaktadır. Bunlar majör depresyon ve bipolar bozukluklar şeklinde ortaya çıkabilmektedir. Bu bozuklukların, sıklıkla MS'in kronik seyri ve kişiyi zamanla sakat bırakan özelliğine sekonder olarak geliştiği kabul edilmektedir. Ayrıca, bazı affektif bozuklukların direkt olarak demiyelinizan lezyonlara bağlı belirtiler olabileceği de iddia edilmektedir. Psikiyatrik bir hastalık öyküsü olmayan, akut mani tablosu ile başvuran ve yapılan incelemeler sonunda, yeni bir MS atağı geçirdiği belirlenen bir olgu sunuldu.

One of the frequent complications of Multiple Sclerosis is the psychiatric disorders. Among these are major depression, manic episodes and bipolar conditions. These condition are believed to be induced by the chronic course of multiple sclerosis. Also the possibility of being handicapped as a result of multiple sclerosis seems to precipitate the occurrence of psychiatric diseases. In recent years, there are reports implying that demyelination lesions observed in multiple sclerosis might have causative effects on behavioral disorders. In the current case report, a subject was presented with acute mania features and investigation on the subject indicated that the subject recently experienced a multiple sclerosis attack.
A Multiple Sclerosis Case Presented With Manic Episode Features